Value-Based Healthcare: Fad or Fabulous? - Stephen Duckett (HealthcarePapers, 2019)
Value-based healthcare has entered the lexicon of health service managers and policy makers over the past decade. But translating the idea from a rhetorical device or concept for use in the United States into a policy or action elsewhere is difficult. It has obvious appeal – who can argue against value? In this paper, I discuss the utility of value-based care as a rhetorical device and the complexity of operationalizing it and identifying patient perspectives on value.
Keywords: value from healthcare, public spending, patient preference, health system integration